Optimization of an electrode made from CdS –ZnO nanorods for hydrogen generation from photoelectrochemical splitting of water - Nhat Hieu Hoang; Van Nghia Nguyen; Minh Thuy Doan (My University, 2017)
Optimization of an electrode made from CdS –ZnO nanorods for hydrogen generation from photoelectrochemical splitting of water
Keywords: CdS–ZnO electrode